2016
DOI: 10.1016/j.toxrep.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal content and potential health risk of geophagic white clay from the Kumasi Metropolis in Ghana

Abstract: Geophagia is the craving for non-food substances and commonly practiced among pregnant women and children. Consumption of geophagic clay samples can have serious implications on the health of the consumers as a result of the presence of toxic metals such as Pb, As, Hg and Cd. This study sought to determine the levels of heavy metals in the studied geophagic clay samples and to determine the potential risks of heavy metals as cumulative carcinogenic and non-carcinogenic risks to the health of the consumers via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 14 publications
4
39
0
1
Order By: Relevance
“…Lead concentrations were observed to be below the mean exposure levels and was in contrast with findings of range of values 549-622.92 µg/Kg reported by Nkansah et al [27]. In line with our results, Tayie et al [10] reported 2.36 ± 0.08 mg/100g.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Lead concentrations were observed to be below the mean exposure levels and was in contrast with findings of range of values 549-622.92 µg/Kg reported by Nkansah et al [27]. In line with our results, Tayie et al [10] reported 2.36 ± 0.08 mg/100g.…”
Section: Discussionsupporting
confidence: 78%
“…Tayie et al [10] reported 0.0 (nil) mg/Kg of Arsenic in clay samples in Accra were found to be lower than results obtained in this study. However, Nkansah et al [27] reported a range of 218-271 ppm from clay samples obtained from different parts of Kumasi Metropolis. Furthermore, Doe et al [32] also reported Arsenic levels of range 2.7-22.74 µg/g in nine (9) samples of clay samples collected from both Greater Accra and Kumasi of Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…These levels were within the safe levels of 80.0 µg/g 17 . One study observed a mean of 6.5 µg/g of Pb in geophagy soil in Tanzania 6 , while another study also reported 27.70±2.90 µg/g of Pb in geophagic white clay at Abuakwa in the Ashanti region of Ghana 18 . The lead levels in the samples from Mankessim were lower than the levels reported from other regions, where the clay is eaten directly.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study revealed that exposure to Lead may cause intelligence decline in children and as well as cancer in adults [49]. Consumption of these clayey samples over a long time may result in serious health effects such as coma, seizure, the dysfunctioning of the kidney, liver and heart of the consumers [50]. Lead targets multiple organs in the human body due to its systemic toxicity which can lead to cardiovascular, renal, gastro-intestinal and haematological effects [50].…”
Section: Physico-chemical Characterizationmentioning
confidence: 99%
“…Consumption of these clayey samples over a long time may result in serious health effects such as coma, seizure, the dysfunctioning of the kidney, liver and heart of the consumers [50]. Lead targets multiple organs in the human body due to its systemic toxicity which can lead to cardiovascular, renal, gastro-intestinal and haematological effects [50]. Neurotoxicity, carcinogenicity and reproductive failures in adults are some of the effects of exposure to Lead (Pb) as contained in the data from the European Food Safety Authority (EFSA) [51].…”
Section: Physico-chemical Characterizationmentioning
confidence: 99%